Physical culture in the context of modern philosophical anthropology - Bogdan Mytskan; Tetiana Mytskan; Sergii Iermakov; Tetiana Yermakova (IP Iermakov S.S., 2022)
Background and study aim. Prerequisites and purpose of the study. Today, philosophical anthropology (in the context of physical culture) occupies an intermediate place between the biological sciences and existential philosophy, elements of which it uses to explain the problems of physical existence. In the deep spheres of the physical state of a man (in the continuum of his/her spiritual-moral, physical, subconscious-rational, irrational and anthrobiological subjectivity) one can find the true foundations of personal physical culture and give them an immanent-subjective expression of human strength (as a creator of culture globalized world). The purpose of the study is to characterize the physical culture of the individual in the context of philosophical anthropology. Material and methods. Sources of information were the authoritative database Web of Science Core Collection, Vernadskyi National Library of Ukraine. Extraction of data from documents was carried out by means of a search query. In total, data on 102 documents containing such keywords as philosophy, anthropology, physical culture, sport were removed from the Web of Science Core Collection. Accordingly, 18 documents were found in the catalogues of the Vernadskyi National Library of Ukraine. Further analysis was performed with these 120 documents. The results of the search query were recorded in the form of tables and a special text file, which was processed in VOSviewer. The requirements of dialectical logic, comparative method, method of phenomenological reduction, hermeneutic methods are chosen by research methods. Results. The most significant and popular thematic categories, journals, authors, articles, keywords are identified. The connection between the elements of bibliographic description of articles and individual groups of publications has been established. It is established that from the second quarter of the XX century among philosophers there is opposition to the understanding of human nature on the basis of the acceptance of some one of its essence (spiritual, physical, intellectual, emotional and volitional, etc.), which determines the existence of any person. This was a denial of the approach to a man, which was called essential (from the Latin essentia - essence). The result of this transformation was to establish an existential understanding of a man (from the Latin existentia - existence). However, a self-contained existential approach is capable of producing a worldview distortion of personal physical culture, especially in conditions of restriction of freedom (for example, during a pandemic, war). Therefore, in modern philosophical anthropology it is necessary to adhere to a balanced combination of essential and existential understanding of a man in general and his/her physical culture in particular. In this way, philosophical anthropology is able to actualize various structures of worldview, including the values of physical culture. Conclusions. From the point of view of modern philosophical anthropology, athletes, in the broadest sense of the term (all those who purposefully engage in physical and sports exercises), are carriers of a set of socio-cultural values (moral and volitional qualities, morpho-functional properties, psychophysical abilities, etc.). These values, in the context of the globalization of civilizational development and the main axiological concepts (quality and standard of living, social order, well-being), should be considered as a means of activating planetary socio-cultural development.